Tradisi Tingalan di Dusun Sibarong dalam Perspektif Living Teologi Islam - Fiqi Restu Subekti; H. Zuhri (AHKAM, 2026)
Although the concept of weton in the Javanese calendar has long been part of religious and cultural practice, studies that specifically examine the tradition of Tingalan or slametan weton as an expression of Islamic theology and local knowledge of one’s position in the cosmos remain limited. This study aims to uncover the theological values embedded in the practice of Tingalan in Sibarong and to explain how this tradition integrates Islamic teachings with local wisdom concerning the relationship between humans, nature, and God. The research employed a qualitative approach with a case study design, using participatory observation and in-depth interviews with religious leaders, community elders, and ritual practitioners as key informants. The findings show that the Tingalan tradition encompasses several core theological dimensions, including the affirmation of tauhid through the recitation of syahadat and tahlil, the manifestation of gratitude through the utterance of alhamdulillah and communal meals, the reinforcement of prayer and tawakal, sedekah as an expression of social solidarity, belief in barokah, and a cosmological awareness that interrelates humans, nature, and God. The results also indicate a pattern of continuity and adaptation, reflected in changes to the frequency of performance and the simplification of ritual elements in response to socio-economic transformations, without eroding the core theological meaning. In conclusion, the Tingalan tradition in Sibarong can be understood as a form of ilmu titen (inner awareness), namely local knowledge of the self’s relationship with nature within the framework of a lived Islamic faith, as well as a religious expression internalized in local cultural practice that contributes to the preservation of Javanese Islamic local wisdom.